1995
DOI: 10.1007/bf01443738
|View full text |Cite
|
Sign up to set email alerts
|

Reaction studies of carbon clusters

Abstract: Abstract. Reaction studies of carbon clusters C, in the range n = 8-37, produced by laser vaporisation in a supersonic nozzle, have been investigated using time-offlight mass spectrometry. Clear differences in reaction products formed on hydrogenation are detected which show that even and odd clusters behave quite differently and furthermore that at least two different types of even cluster appear to exist. The reactivity patterns for clusters C, with n = t6, 18 and 22 are in a different class from those with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…Hallett et al 10 have studied the carbon clusters in the range n ) 8-37, produced by laser vaporization in a supersonic nozzle and investigated with time-of-flight (TOF) mass spectrometry confirming the existence of C 26 , C 28 , and other small fullerenes. C 28 fullerene has been known to be the smallest fullerene molecule and becomes stable as M@C 28 (M ) Ti, Mg, etc.).…”
Section: Methodsmentioning
confidence: 99%
“…Hallett et al 10 have studied the carbon clusters in the range n ) 8-37, produced by laser vaporization in a supersonic nozzle and investigated with time-of-flight (TOF) mass spectrometry confirming the existence of C 26 , C 28 , and other small fullerenes. C 28 fullerene has been known to be the smallest fullerene molecule and becomes stable as M@C 28 (M ) Ti, Mg, etc.).…”
Section: Methodsmentioning
confidence: 99%
“…302 In some of these studies, information about the neutral structures was obtained by seeding the reactant in the carrier gas of a laser vaporizationsupersonic expansion source. [294][295][296] Neutral species formed in the expansion were then ionized and observed using time-of-flight mass spectrometry. Long polyacetylenic chains (HC n H, n e 40) were thought to be present with H 2 as the reactant gas, leading to the conjecture that neutral carbon chains of this size may be forming.…”
Section: Ion−molecule Reactivity Studiesmentioning
confidence: 99%
“…These studies of course provide much useful information about the ion−molecule chemistry of carbon cluster ions. In recent years, carbon cluster cation structural and reactive properties have been investigated by reactions with such species as H 2 , O 2 , N 2 O, benzene, naphthalene, nitriles, , chloropropenes, and polyaromatic hydrocarbons . Pozniak and Dunbar recently showed that C 10 + to C 24 + ions whose cyclic isomers satisfied the conditions for aromaticity were less reactive than the other ions in this size range …”
Section: Ion−molecule Reactivity Studiesmentioning
confidence: 99%
“…Consensus of opinion now favours closed shell fullerene structures for the C32-C 100 clusters, with each containing, by definition, the twelve pentagons required for closure (Euler's rule) plus (n -20)/2 hexagons. There is now convincing all fullerenes (C20, C24 ...) may form from graphite (Kroto 1987;Hallet et al 1992), however, the mechanism is very much an open question, with concrete evidence hard to come by. One possibility would be for long polyyne chains, formed from C2 or C4 units, to spirocyclize forming a complete or part fullerene.…”
Section: Fullerenes From Polyynesmentioning
confidence: 99%